The Role Of Ppkn Learning In Improving Morality As A Prevention Alternative Student's Delivery In Sma Negeri 1 Bangun Ancient Year Of Study 2020/2021 - Habeahan, Sampitmo; Salwa Annisa Siregar, Putri; Hodriani, Hodriani (International Journal of Educational Research & Social Sciences, 2021)
This study aims to determine the role of Civics learning in improving morality as an alternative to delinquency prevention for class XI students of SMA Negeri 1 Bangun Purba, Deli Serdang Regency, North Sumatra Province. The method used in this research is descriptive quantitative method. This research consists of two variables. Data collection techniques used are the distribution of questionnaires (questionnaires) and documentation. Total population, namely all students of class XI totaling 178 students. The sample taken in this study were 27 students, namely 15% of the total population using random sampling technique. The data analysis technique using Correlation Test, Determination Test and Hypothesis Testing. The results of this study indicate that there is an influence on the role of Civics in improving morality as an alternative to preventing student delinquency, which has a very good effect. From the results of calculations using product moment correlation, rcount is 0.6917 while rtable at n-2 = 27-2 = 25 at an error rate of 5% is 0.3809, thus the price of rcount > rtable is 0.6917 > 0.3809 so that the correlation coefficient variable X and variable Y are significant and classified as strong. Based on the hypothesis test, it is obtained that tcount > ttable, then tcount = 4.76 > 2.0595 at a significant level of 5% so that the alternative hypothesis states that there is an Influence of the Role of Civics Learning in Improving Morality as an alternative to preventing student delinquency in SMA Negeri 1 Bangun Purba in the 2020 Academic Year/ 2021 is acceptable.